2017
DOI: 10.1371/journal.pntd.0005377
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of gut microbiota of mosquito communities in central Illinois

Abstract: BackgroundThe composition and structure of microbial communities that inhabit the mosquito midguts are poorly understood despite their well-documented potential to impede pathogen transmission.Methodology/Principal findingsWe used MiSeq sequencing of the 16S rRNA gene to characterize the bacterial communities of field-collected populations of 12 mosquito species. After quality filtering and rarefaction, the remaining sequences were assigned to 181 operational taxonomic units (OTUs). Approximately 58% of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
103
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 73 publications
25
103
2
Order By: Relevance
“…Recent similar methods using 16S rRNA amplicon sequencing to determine the overall microbiota in wild mosquito populations has provided evidence for Wolbachia infections in An. gambiae in additional villages in Burkina Faso [54] and Anopheles species collected in Illinois, USA [55]. Our study describing resident Wolbachia strains in numerous species of Anopheles malaria vectors also highlights the potential for Wolbachia to be influencing malaria transmission, as postulated by previous studies [39,40,56].…”
Section: The Mosquito Microbiota Can Modulate the Mosquito Immune Ressupporting
confidence: 75%
“…Recent similar methods using 16S rRNA amplicon sequencing to determine the overall microbiota in wild mosquito populations has provided evidence for Wolbachia infections in An. gambiae in additional villages in Burkina Faso [54] and Anopheles species collected in Illinois, USA [55]. Our study describing resident Wolbachia strains in numerous species of Anopheles malaria vectors also highlights the potential for Wolbachia to be influencing malaria transmission, as postulated by previous studies [39,40,56].…”
Section: The Mosquito Microbiota Can Modulate the Mosquito Immune Ressupporting
confidence: 75%
“…The results suggested that Burkholderia and Ralstonia might be the vital components of the gut bacteria in the three spider species, and the relative abundance of these two bacteria in the spider guts may affect the distribution and abundance of the other bacteria. In regard to other bacteria identified in this study (more than 0.1% of total reads), Propionibacterium, Morganella, Providencia, Sphingomonas, Chryseobacterium, and Corynebacterium were also found in the guts of mosquitoes (Charan et al, 2016;Manguin, 2013;Muturi et al, 2017). Lactococcus, Lactobacillus, Pseudomonas, Paracoccus, Microbacterium, Serratia, Achromobacter, Bacillus, and Agrobacterium were also found in the guts of Lepidoptera (Chen et al, 2016;Snyman et al, 2016), and Serratia are known to contain hemolytic enzymes and could play a potential role in blood digestion (Gaio et al, 2011) Moran, & Hunter, 2003).…”
Section: Discussionmentioning
confidence: 67%
“…In recent years, researchers have become increasingly interested in the gut bacteria of arthropods with the advent of next‐generation sequencing (NGS) technology. The diversity of gut bacteria has been studied in a range of insects and ticks (Anjum et al, ; Muturi, Ramirez, Rooney, & Kim, ; Snyman, Gupta, Bezuidenhout, Claassens, & Van dBJ, ; Waite et al, ). Gut bacteria have a great impact on their insect hosts, such as resistance against parasites and pathogens (Dillon, Vennard, & Charnley, ; Koch & Schmid‐Hempel, ), nutrient supplementation (Eichler & Schaub, ; Hongoh et al, ), intestinal cell renewal and developmental rate (Shin et al, ), and digestion of dietary compounds (Gaio et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent similar methods using 16S rRNA amplicon sequencing to determine the overall microbiota in wild mosquito populations has provided evidence for Wolbachia infections in An. gambiae in additional villages in Burkina Faso 71 and Anopheles species collected in Illinois, USA 72 . Our study describing resident Wolbachia strains in numerous species of Anopheles malaria vectors also highlights the potential for Wolbachia to be influencing malaria transmission, as postulated by previous studies 39, 40, 73 .…”
Section: Discussionmentioning
confidence: 99%